Analisis Risiko Kerja pada Petugas Koding Rawat Jalan di RSUP Dr. Kariadi Semarang - Irda Nazia Safitri; Feby Erawantini; Mochammad Choirur Roziqin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Outpatient coding of RSUP Dr. Kariadi has an average of 240 file targets to be coded for each officer, coding activity can trigger work risks such as stress, loss of concentration and illness due to work fatigue. The purpose of this study was to Analyze the occupational risks of outpatient coding officers in RSUP Dr. Kariadi Semarang. This type of research is a descriptive study with an interview and observation approach. The object of this study was outpatient coding officer in RSUPÂ Dr.Â Kariadi. The results showed that the risks in outpatient coding officers there are 5 risks that can occur. Risks regarding workplace accidents as well as work system risks can be found in outpatient coding. The solution is to create an SOP on the safety of outpatient coding officers.